Sister-queens in the high Hellenistic period - Llewellyn-Jones, Lloyd, author.
1 online resource (xii, 276 pages)
Keywords: "Sister-Queens in the High Hellenistic Period is a cutting-edge exploration of ancient queenship and the significance of family politics in the dysfunctional dynasties of the late Hellenistic world. This volume, the first full-length study of Kleopatra III and Kleopatra Thea and their careers as queens of Egypt and Syria, thoroughly examines the roles and ideology of royal daughters, wives, and queens in Egypt, the ancient Near East, and ancient Israel and provides a comprehensive study of the iconography, public image, and titles of each queen and their cultural precedents. In addition, this book also offers an introduction to the critical concept of the 'High Hellenistic Period' and the maturation of royal female power in the second century BCE. Sister-Queens in the High Hellenistic Period is suitable for students and scholars in ancient history, Egyptology, classics, and gender studies, as well as the general reader interested in ancient queenship, ancient Egypt, the Hellenistic world, and gender in antiquity"--